1999
DOI: 10.1177/00912709922007903
|View full text |Cite
|
Sign up to set email alerts
|

DHEA and DHEA‐S: A Review

Abstract: Dehydroepiandrosterone (DHEA) and its sulfated metabolite DHEA-S are endogenous hormones secreted by the adrenal cortex in response to adrenocorticotrophin (ACTH). Much has been published regarding potential effects on various systems. Despite the identification of DHEA and DHEA-S more than 50 years ago, there is still considerable controversy as to their biological significance. This article reviews the metabolism and physiology of DHEA and DHEA-S, the influence of age and gender on concentrations, and change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
342
1
19

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 481 publications
(386 citation statements)
references
References 131 publications
15
342
1
19
Order By: Relevance
“…DHEAS is more soluble in water than DHEA, is converted to DHEA in the cerebral tissue (Kroboth et al, 1999), and is reported to affect the brain neurotransmitter receptors (GABA A R, NMDAR, s1R) in the same mode as DHEA (Majewska, 1992;Monnet et al, 1995;Urani et al, 2001). Therefore, DHEAS was used for the direct intrabrain administration.…”
Section: Discussionmentioning
confidence: 99%
“…DHEAS is more soluble in water than DHEA, is converted to DHEA in the cerebral tissue (Kroboth et al, 1999), and is reported to affect the brain neurotransmitter receptors (GABA A R, NMDAR, s1R) in the same mode as DHEA (Majewska, 1992;Monnet et al, 1995;Urani et al, 2001). Therefore, DHEAS was used for the direct intrabrain administration.…”
Section: Discussionmentioning
confidence: 99%
“…DHEAS is much more abundant than DHEA, because DHEAS has longer half-life and lower clearance (Lennartsson et al, 2012). Because DHEAS levels are also more stable and show no diurnal variation (Kroboth et al, 1999), they are often preferred in studies on long term effects of stress. Studies on acute stress, on the other hand, often assess DHEA, since DHEAS serves as a reservoir for DHEA biosynthesis and DHEA rather than DHEAS is expected to respond to acute psychosocial stress (Izawa et al, 2008;Morgan et al, 2004;Oberbeck et al, 1998;Pico-Alfonso et al, 2004;Shirotsuki et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The two enzymes also showed low K m values (Յ1 mM) for 17-ketosteroids, of which DHEA and its sulfate are known to exert a variety of biological actions. 25,26) 16-Ketoestrone was efficiently reduced by the enzymes. In contrast to the low catalytic efficiency (k cat /K m ) for estrone.…”
mentioning
confidence: 99%
“…37) Thus, the kidney is a major organ that metabolizes DHEA and its sulfate, although further study will be needed to elucidate the relationship between the metabolism and various biological actions of DHEA and its sulfate. 25,26) Furthermore, the expression of the two isoforms of 3(17)a-HSD in mouse brain may be important for controlling the concentrations of neuroactive steroids. DHEA sulfate, a substrate of the enzymes, is not only a positive modulator of the s1 receptor, but also a negative modulator of the GABA A -receptor.…”
mentioning
confidence: 99%